PrevalÊNcia, etiologia E fatores de risco de mastite subclínica em rebanhos leiteiros de viÇosa-MG - Da Cunha, Adriano França; Bragança, Lindomar José; Quintão, Leonardo Cotta; Silva, Simone Quintão [UNESP]; De Souza, Fernando Nogueira; Cerqueira, Mônica Maria Oliveira Pinho (My University, 2015)
The prevalence, causative agents and factors related to management practices and production characteristics that influenced subclinical mastitis were determined in 44 dairy farms of Viçosa-MG. In 617 cows, subclinical mastitis was diagnosed by California Mastitis Test. Milk samples from animals with mastitis were submitted to microbiological tests for confirmation of the disease. A structured questionnaire was used to determine the risk factors of mastitis. The prevalence of subclinical mastitis in herds were 55.4%. The etiological agents more isolated were Corynebacterium sp. (32.99%), Staphylococcus aureus (28.35%), Streptococcus agalactiae (13.66%), Staphylococcus coagulase negativo (13.66%) and Staphylococcus intermedius (6.19%). The low milk production, inadequate procedure of milking, supplying of disposal milk to calves, lack of mastitis treatment during the dry period, poor hygiene of cows environmental and bad quality of water in farms had significant association (p < 0.05) with the prevalence of subclinical mastitis. Better care of the milking practices and management of the property are necessary in farms of Viçosa-MG.
Prevalence, etiology and risk factors of subclinical mastitis in dairy cattle of Viçosa-MG
Keywords: Bacteria; Management; Mastitis; Sanity; Udder